2008
DOI: 10.1111/j.1440-1843.2008.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

The burden of lung disease in Hong Kong: A report from the Hong Kong Thoracic Society

Abstract: Respiratory disease is responsible for the highest health-care burden locally. Increased efforts in improving management and prevention of these diseases, including tobacco control, improving air quality and vaccination against influenza and pneumococci, are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 104 publications
(124 reference statements)
1
44
1
Order By: Relevance
“…(16) A report from the UK revealed that 39% of bed days used for respiratory disease treatment are due to pneumonia and other acute lower respiratory infections. (5) A survey conducted in Hong Kong (20) showed that respiratory infections were a major cause of utilization of respiratory inpatient bed days. These differences in the ranking of respiratory diseases might be attributed to the interaction of environmental factors, smoking, HIV infection and poverty in the developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…(16) A report from the UK revealed that 39% of bed days used for respiratory disease treatment are due to pneumonia and other acute lower respiratory infections. (5) A survey conducted in Hong Kong (20) showed that respiratory infections were a major cause of utilization of respiratory inpatient bed days. These differences in the ranking of respiratory diseases might be attributed to the interaction of environmental factors, smoking, HIV infection and poverty in the developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria for patients comprised: (1) no family caregiver at home (n ¼ 597); (2) inability to speak the Cantonese dialect or lack of a permanent residence in Hong Kong (n ¼ 90); and (3) failure to perform the spirometry test (n ¼ 10).…”
Section: Participantsmentioning
confidence: 99%
“…Silicosis results from the inhalation of silica dust from mines and quarries, 1 and is the most common type of pneumoconiosis in Hong Kong. Its main symptoms include coughing and shortness of breath, and its complications include emphysema and tuberculosis.…”
mentioning
confidence: 99%
“…2 A territory-wide survey of the burden of lung disease in Hong Kong in 2005 showed that COPD was the second most common respiratory cause of hospitalisation (accounting for 14.6% of admissions and 20.5% of in-patient bed-days). 3 However, the hospitalisation data of that 2005 survey only included the principal diagnosis on discharge. There was no information on the severity of airflow limitation, co-morbidities, admission pattern, or long-term treatments.…”
Section: Introductionmentioning
confidence: 99%